Penegakan Hukum Persaingan Usaha Di Negara Berkembang - Mansur Amin Bin Ali (Fakultas Hukum Universitas Mataram, 2016)
The development of international economic very dynamically not only regulate international economic regulation but also for national competition law aspects. It is have relation with state sovereignty in law enforcement affairs. The sovereignty Indonesia as a state to regulate competition law is right of Indonesian as international subject law. But the entity of other state have opportunity to appellate the regulation of a state through national legal mechanism. Further that the decide of commission of competition law in Temasek case as realization of state sovereignty that recognized by international law and Singapore has obliged to respect to these decide.